Placental and serum malondialdehyde changes In different gestational ages - ZEENA A. ABID ALI MSC; MAY F. AL-HABIB PHD; RAYAH S. BABAN PHD (International Journal of Pharma and Bio Sciences, 2018)
Body defense response involves enzymatic and non-enzymatic antioxidant buffering pathways which reduce the effect of these free radicals. Previous studies have shown that increasing level of oxidative stress biomarkers may lead to pregnancy complications. This study aimed to assess the correlation between oxidative stress level and pregnancy duration. A case-control study design was employed in this study. Ninety pregnant women were selected (30 term women were selected as the study control, 30 preterm women as the first case group, and 30 post-term women as the second case group). Prior to admission of enrolled women to operation theatre, blood and Placental tissue samples were also collected after delivery. Blood and urine samples were used to measure Malondialdehyde (MDA). Placental tissue were prepared and stained for histological assessment Anti-MDA. The result showed that oxidative stress biomarker in blood (MDA) is high among preterm women group and low among post-term women group. The histological examination of placental tissue from preterm, term and post-term women groups revealed that preterm women group had the lowest reactivity with both anti-MDA in comparison to term women group. On the other hand, post-term women group had the highest reactivity of anti-MDA antibody in the placental tissue. In conclusion, preterm pregnancy was associated with increased oxidative stress and decreased anti-oxidant activity. In contrast, post-term pregnancy was associated with low oxidative stress status and high anti-oxidant activity.